Critical discourse analysis of cultural representations in EFL national commercial textbooks - Diah Ayuni Ariawan; Joko Nurkamto; Sumardi Sumardi (Universitas Syiah Kuala, 2022)
Mastering grammar and vocabulary in communication are seemingly insufficient for learners to communicate with different societies worldwide. For this rationale, cultures in ELT materials took a pivotal role in equipping learners with intercultural communicative competence (ICC). Hence, the researchers critically analyze two national commercial textbooks commonly used in senior high schools for the tenth and eleventh grades in any area to examine the elements of cultures and their representations. The researchers address this gap by adopting critical discourse analysis (CDA) to get a profound interpretation of data. The textual data was categorized, coded, counted, and finalized by creating a description. The result revealed that these textbooks contained elements of cultures; product (63%, 44%), person (13%, 42%), practice (19 %, 8%), and perspective (5%, 6%) in different proportions. The result also points out that there is an unbalance among culture-related items with 59%, 51% in source cultures, 11% and 26% in target, and 17% and 8% in international, which means target and international cultures are less than source cultures. This research also found universal cultures relating to cultures free in these textbooks with 13% and 18%, respectively. The finding indicated that both textbooks have imbalanced cultures, which means that target and international cultures were under-represented. The researchers suggest that other Southeast Asian, African, and Russian cultures must be considered in the textbooks. Furthermore, this research expects the stakeholders to be more concerned with designing, concerning, and choosing suitable textbooks to equip learners with diverse cultures.